"Can I go into the artwork?" Material-relational situations with abstract art - Heidi Kukkonen (Cappelen Damm Akademisk NOASP, 2022)
The purpose of this article is to study museum educational situations, where 5-7-year-old children encounter abstract art, from a new materialist perspective. The children visit an exhibition curated by me, where abstract modernist art is mediated, with an emphasis on multisensory experiences and experimentation. The visits were recorded with stationary and action cameras. By focusing on material-relational situations, I investigate how learning takes place when the children engage with the museum educational setting. A girl asks a surprising question that challenges the takenfor-granted beliefs about what art can be. The children break rational and logical patterns by creating abstract art, and "aesthetic-intuitive order" takes place in the compositions. A child and an adult relate differently to the agential "teaching matter." Embodied and material pedagogy with abstract art indicates how "making sense" of the world is not only done in verbal and logical ways but also by experimenting with bodies and senses with teaching matter.